1999
DOI: 10.1038/sj.gt.3300831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chimeric immune receptor extracellular protein domains on T cell function

Abstract: Chimeric immune receptors (CIR) encompass tumor-or were constructed to include alternative extracellular spacer virus-specific ligands or antibodies fused to the signaling and transmembrane protein domains derived from memdomains of either the T cell receptor or Fc receptor. T cells bers of the immunoglobulin supergene family. The effect of expressing these receptors recapitulate the cytopathic these alternative extracellular protein domains on receptor effects mediated by the T cell receptor and allow the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…For example, changes to the hinge region may result in improved function as has been demonstrated previously for some chimeric receptors. [30][31][32] It is not clear what proportion of the bulk T cell population were dual specific at a single cell level, although all T cells had integrated the retroviral gene encoding the chimeric receptor and neomycin phosphotransferase, since the neomycin analog G418 was used in the cell culture period. Some insight into the likely Antitumor dual-specific T cells A Murphy et al proportion of dual-specific T cells can be gained from previous studies that characterized human dual-specific T cells, which are readily cloned (in contrast to mouse T cells), where 30-40% of T cells in the bulk population were demonstrated to be reactive with two antigens following transduction with a chimeric receptor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, changes to the hinge region may result in improved function as has been demonstrated previously for some chimeric receptors. [30][31][32] It is not clear what proportion of the bulk T cell population were dual specific at a single cell level, although all T cells had integrated the retroviral gene encoding the chimeric receptor and neomycin phosphotransferase, since the neomycin analog G418 was used in the cell culture period. Some insight into the likely Antitumor dual-specific T cells A Murphy et al proportion of dual-specific T cells can be gained from previous studies that characterized human dual-specific T cells, which are readily cloned (in contrast to mouse T cells), where 30-40% of T cells in the bulk population were demonstrated to be reactive with two antigens following transduction with a chimeric receptor.…”
Section: Discussionmentioning
confidence: 99%
“…6 Like ␥ chain receptors, the spacer domain affects the affinity of chain receptors for ligand and impairs receptor-mediated cytolysis. 8 Therefore, the high impact of an extracellular constant domain on the signaling function of recombinant receptors calls for a more rational design of the receptor molecule based on the modular components, particularly the signaling domain. Due to stable expression without the necessity of a spacer domain, we suggest that the basic scFv-␥ chain receptor configuration is preferred in the application of the chimeric receptor strategy in order to avoid that the extracellular spacer domain itself impairs receptor-mediated signaling and cellular activation.…”
Section: Discussionmentioning
confidence: 99%
“…7 Due to the lack of a rationale design and systematic determination of an optimal receptor configuration, it is still a matter of controversy whether modification of the basic receptor configuration by insertion of an heterologous protein spacer domain affects binding to ligand and/or transduction of the cell activation signal. Recently, Patel et al 8 reported that different extracellular spacer domains of a recombinant receptor harboring a CD3 signaling domain impair receptor-mediated target cell lysis. The stability of chain receptor expression itself, however, depends substantially on an appropriate spacer domain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that dependent on the intracellular signalling domain and the type of grafted effector cell, the recombinant receptor may require an additional extracellular spacer domain for stable expression 11,12 that in turn also impacts its cell activation properties. 10,11 A rational design for the generation of highly efficient recombinant T-cell immunoreceptors must address both the receptor's cell surface expression and its cell activation properties that in turn modulate effector cell activation during prolonged propagation of receptor grafted T cells and the functional discrimination of membrane bound versus soluble target antigen required for efficient target cell elimination. On the other hand, our growing knowledge about the function of modularily composed immunoreceptors facilitates also the generation of receptors that exhibit restricted cellular activation properties thereby limiting the cellular response upon repeated restimulation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Recombinant z-chain receptors, in contrast to g-chain receptors, require an extracellular spacer domain for functional expression in T cells. 12 Although the requirements for functional expression of recombinant g-and z-chain receptors are obviously different, it remains unresolved how the transmembrane and/or intracellular signalling domain affects the stability of recombinant receptor expression on the cell surface and receptor-mediated cellular activation of grafted T cells.…”
Section: Introductionmentioning
confidence: 99%